2014
DOI: 10.3389/fmicb.2014.00515
|View full text |Cite
|
Sign up to set email alerts
|

The ecological dichotomy of ammonia-oxidizing archaea and bacteria in the hyper-arid soils of the Antarctic Dry Valleys

Abstract: The McMurdo Dry Valleys of Antarctica are considered to be one of the most physically and chemically extreme terrestrial environments on the Earth. However, little is known about the organisms involved in nitrogen transformations in these environments. In this study, we investigated the diversity and abundance of ammonia-oxidizing archaea (AOA) and bacteria (AOB) in four McMurdo Dry Valleys with highly variable soil geochemical properties and climatic conditions: Miers Valley, Upper Wright Valley, Beacon Valle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
45
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 66 publications
8
45
0
1
Order By: Relevance
“…In cold soil environments, archaeal diversity appears to increase with soil depth, probably due to the increased anaerobic status of deeper soils [43]. In both Antarctic and Arctic soils, Thaumarchoeota dominate, with a high abundance of Nitrososphaerales lineages [44][45][46]. It has been speculated that Thaumarchoeota may be important heterotrophs in depauperate soils, where their capacity to utilise recalcitrant organic substrates such as methane, short-chained alkanes, chlorinated ethanes and aromatic hydrocarbons may contribute significantly to the energy balance of the community [47].…”
Section: Microbial Diversity In Cold Environmentsmentioning
confidence: 99%
“…In cold soil environments, archaeal diversity appears to increase with soil depth, probably due to the increased anaerobic status of deeper soils [43]. In both Antarctic and Arctic soils, Thaumarchoeota dominate, with a high abundance of Nitrososphaerales lineages [44][45][46]. It has been speculated that Thaumarchoeota may be important heterotrophs in depauperate soils, where their capacity to utilise recalcitrant organic substrates such as methane, short-chained alkanes, chlorinated ethanes and aromatic hydrocarbons may contribute significantly to the energy balance of the community [47].…”
Section: Microbial Diversity In Cold Environmentsmentioning
confidence: 99%
“…Nitrogen can also be sourced from the atmospheric deposition of nitrate salts, which tend to accumulate in dry and high-altitude valleys due to the absence of vegetation as well as to the aerobic conditions of the soils which inhibit reductive pathways of the N cycle, such as denitrification [11]. As such, nitrification may be an important biological process for N cycling and the productivity of terrestrial polar systems [12][13][14]. Nitrification comprises two main reactions, generally carried out by different microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the diversity of the community can potentially help to neutralize the effects of disturbance through spatial or temporal rearrangements of these smaller populations, with important implications for the process stability [22]. Although not extensively analyzed, the presence/absence, diversity, and structure of nitrifying communities have been assessed in different regions of Antarctica, namely in continental shelf waters and across a latitude gradient in the Antarctic Peninsula [7,12] and in the McMurdo Dry Valleys soils and lakes from the Ross Sea region [14,23,24]. These studies have concluded that environmental variables such as water availability and soil geochemistry are correlated with the distribution, abundance, and diversity of different nitrifying groups and could be driving a niche specialization and differentiation between AOA and AOB communities in the soils [14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations